Recent developments in stimuli‐responsive hydrogels for biomedical applications. Issue 4 (13th October 2022) - Liu, Shuyun; Li, Xiaozhuang; Han, Lu
Abstract: Hydrogels exhibit a performance similar to that of the extracellular matrix and are compatible with human tissues and organs. Stimuli‐responsive hydrogels that can respond smartly to a variety of stimuli have recently attracted extensive interest for biomedical applications. The response of these hydrogels to various single/multiple stimuli shows great potential for drug delivery, biosensors, wound dressing, cancer therapy, and tissue engineering. This review summarises the recent advances in the design of different stimuli‐responsive hydrogels and their biomedical applications. We herein describe the mechanisms underlying the stimulus–response, and summarise the strategies for fabricating stimuli‐responsive hydrogels that can respond to single or multiple stimuli from endogenous (i.e. pH, enzymes, glucose, and reactive oxygen species) or exogenous (i.e. magnetic and electric fields, temperature, and photo) sources. The current challenges faced by stimuli‐responsive hydrogels are discussed and an outlook on future research directions is provided.